Sulfide composite solid-state positive electrode, preparation method thereof and all-solid-state battery

Through alternating coating, the sulfide electrolyte is uniformly distributed in the composite positive electrode of all solid state batteries, which solves the problem of poor interface compatibility between the sulfide electrolyte and the positive electrode material, and realizes the sulfide composite with high ionic conductivity and high surface load. Solid-state positive electrode avoids the necessity of high-temperature treatment.

CN119400796APending Publication Date: 2025-02-07WEICHAI POWER CO LTD

Patent Information

Application Number
CN202411557260.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, when preparing the composite positive electrode of an all-solid state battery, the interface compatibility between the sulfide electrolyte and the positive electrode material is poor, resulting in high-speed friction and chemical side reactions, and reducing electrochemical performance. Meanwhile, existing methods require high temperature treatment to restore conductivity, damaging the adhesive network and electrode structure.

Method used

The sulfide composite solid positive electrode is prepared by alternating coating method, by coating the sulfide electrolyte dispersion on the positive electrode layer with a pore structure, it is uniformly distributed, and dried at a lower temperature to avoid a decrease in conductivity.

Benefits of technology

The uniform distribution and high surface load of sulfide electrolyte are achieved, the problem of insufficient penetration of electrolyte is avoided, the high ionic conductivity is maintained, the high temperature treatment is not required, and the process is highly operable, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400796A_ABST
    Figure CN119400796A_ABST
Patent Text Reader

Abstract

The invention provides a sulfide composite solid-state positive electrode, a preparation method thereof and an all-solid-state battery. The preparation method comprises the following steps: (1) coating the surface of at least one side of a current collector with positive electrode slurry, and drying to obtain a positive electrode layer with a pore structure; (2) coating the surface of one side, far away from the current collector, of the positive electrode layer with sulfide electrolyte dispersion liquid, so that the sulfide electrolyte dispersion liquid permeates into the pore structure of the positive electrode layer, and then drying; and (3) repeating the step (1) and the step (2) at least once, and then drying and rolling to obtain the sulfide composite solid positive electrode, wherein the sulfide electrolyte dispersion liquid comprises a sulfide electrolyte and a non-polar solvent, and the sulfide electrolyte and the non-polar solvent are immiscible with each other. According to the preparation method provided by the invention, the sulfide electrolyte can be uniformly distributed in the positive electrode layer in an alternate coating mode, and the ionic conductivity of the sulfide electrolyte is not influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a sulfide composite solid-state positive electrode and a preparation method thereof and an all-solid-state battery. Background Art

[0002] All-solid-state lithium batteries have attracted widespread attention from academia and industry because of their ability to resolve safety risks of liquid batteries and improve battery energy density. Solid-state batteries require the use of solid electrolytes to build a complete lithium ion transmission pathway. Sulfide electrolytes have high room temperature ion conductivity and are soft, making them ideal electrolytes for all-solid-state batteries. In addition to electrode active materials, conductive carbon, and binders, sulfide electrolytes are also required in the pole pieces of solid-state batteries. For pole piece forming technology, wet pulping-coating-drying-compacting is currently the most mature process route with a complete upstream and downstream industrial chain and large-scale production.

[0003] However, the interfacial compatibility between sulfide electrolyte and cathode materials (such as nickel-cobalt-manganese ternary cathode materials) is poor. In the preparation of composite slurry, extremely high shear force is used to disperse the materials in order to improve production efficiency. During the process, violent collisions will occur between the two. Local excessively high temperatures will accelerate the chemical side reactions between the two, seriously reducing the electrochemical performance of the composite cathode. Therefore, developing an appropriate composite cathode forming process to eliminate the side reactions caused by high-speed friction and collision between sulfide electrolyte and cathode materials is of great significance for improving the electrochemical performance of solid-state batteries.

[0004] CN114597339A discloses a method for preparing a positive electrode of a solid-state battery, namely, first forming a positive electrode sheet having only a positive electrode material layer, then dissolving a sulfide electrolyte in a solvent, and then pouring the solution into the porous positive electrode material layer to achieve electrolyte-type wettability coating of the electrode by the sulfide solid electrolyte.

[0005] CN111628139A discloses an all-solid-state battery electrode and its preparation method and use. The method also comprises first preparing a base electrode, then dissolving a sulfide electrolyte in a solvent, and adding an electrolyte insoluble in the solvent to form a composite electrolyte suspension. The suspension is then coated on the surface of the base electrode and finally dried to form a composite positive electrode.

[0006] Although the methods of the above two patents avoid the side reactions caused by high-speed friction and collision between the sulfide electrolyte and the positive electrode material, they both involve the process of dissolving and re-precipitating the sulfide electrolyte. The dissolution process will destroy the original crystal structure of the sulfide. The sulfide re-precipitated during the drying process of the electrode will have a reduced ionic conductivity due to insufficient crystallinity. If you want to restore high conductivity, you need to re-treat it at high temperature (>200°C). The melting point of the binder used in the electrode is generally lower than 200°C. Such an operation is not only long and energy-consuming, but also destroys the original binder network and then destroys the structure of the original electrode. In addition, because the internal pores of the base electrode are disordered, it is impossible to achieve uniform impregnation of the thick base electrode, that is, it is impossible to prepare a thick composite positive electrode.

[0007] Therefore, there is an urgent need to provide a composite positive electrode preparation process that will not reduce the conductivity of the sulfide electrolyte and can achieve uniform impregnation of thick base electrodes. Summary of the invention

[0008] In view of the shortcomings of the prior art, the object of the present invention is to provide a sulfide composite solid-state positive electrode and a preparation method thereof and an all-solid-state battery. The preparation method of the sulfide composite solid-state positive electrode provided by the present invention can make the sulfide electrolyte evenly distributed in the positive electrode layer by alternating coating, and can achieve uniform addition of the sulfide electrolyte in the high-surface-load thick positive electrode, which can avoid the problem that the thick base electrode cannot be fully penetrated and impregnated due to one-time molding; at the same time, in the sulfide electrolyte dispersion of the present invention, the sulfide electrolyte is insoluble in non-polar solvents, and only a lower temperature is required to remove the non-polar solvent in the subsequent drying process, which has no effect on the ionic conductivity of the sulfide electrolyte, thereby avoiding the problem of reduced ionic conductivity caused by dissolution-precipitation of the sulfide electrolyte, and no high-temperature treatment is required to improve the ionic conductivity.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing a sulfide composite solid-state positive electrode, the preparation method comprising:

[0011] (1) The positive electrode slurry is coated on at least one side of the current collector, and after drying, a positive electrode layer having a porous structure is obtained.

[0012] (2) coating a sulfide electrolyte dispersion onto the surface of the positive electrode layer away from the current collector, allowing the sulfide electrolyte dispersion to penetrate into the pore structure of the positive electrode layer, and then drying.

[0013] (3) Repeating step (1) and step (2) at least once (for example, once, twice, three times, five times, eight times, ten times or fifteen times), and then drying and rolling to obtain the sulfide composite solid positive electrode.

[0014] The sulfide electrolyte dispersion includes a sulfide electrolyte and a non-polar solvent, and the sulfide electrolyte and the non-polar solvent are immiscible.

[0015] It will be understood by those skilled in the art that in step (3), when step (1) is repeated, the positive electrode slurry is not coated on the surface of the current collector, but is coated on the surface of the side of the product obtained in step (2) away from the current collector.

[0016] The present invention provides a method for preparing a sulfide composite solid-state positive electrode. By alternating coating, the sulfide electrolyte can be evenly distributed in the positive electrode layer, and the uniform addition of the sulfide electrolyte in the high-surface-load thick positive electrode can be achieved, which can avoid the problem that the thick base electrode is formed at one time and the electrolyte cannot be fully penetrated and impregnated; at the same time, in the sulfide electrolyte dispersion of the present invention, the sulfide electrolyte is insoluble in non-polar solvents, and the microstructure of the sulfide electrolyte has not changed. In the subsequent drying process, only a lower temperature is required to remove the non-polar solvent, which has no effect on the ionic conductivity of the sulfide electrolyte, thereby avoiding the problem of reduced ionic conductivity caused by the dissolution-precipitation of the sulfide electrolyte, and no high-temperature treatment is required to improve the ionic conductivity; in addition, the preparation method of the present invention is highly operable and can be industrially large-scale production. In summary, the preparation method of the present invention can prepare a sulfide composite solid-state positive electrode with controllable surface load and high-speed lithium ion transmission channel.

[0017] Preferably, the positive electrode slurry comprises a positive electrode active material, a conductive agent, a binder and a solvent.

[0018] Preferably, the positive electrode active material includes at least one of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium vanadate and lithium iron manganese phosphate. Exemplarily, the lithium nickel cobalt manganese oxide includes but is not limited to LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811) or LiNi 0.9 Co 0.05 Mn 0.05 O2, etc.

[0019] Preferably, the conductive agent includes at least one of Super P Li, Super C45, Super C65, acetylene black, carbon nanotubes (CNTs), vapor deposited carbon fibers, graphite, graphene, and Ketjen black.

[0020] Preferably, in the positive electrode slurry, the binder includes PVDF (polyvinylidene fluoride).

[0021] Preferably, in the positive electrode slurry, the solvent includes at least one of NMP (N-methylpyrrolidone), DMA (N,N-dimethylacetamide), DMF (N,N-dimethylformamide) and DMSO (dimethyl sulfoxide).

[0022] Preferably, the drying temperature in step (1) is 90-110°C, for example, 90°C, 95°C, 100°C, 105°C or 110°C; the drying time is 2-5 min, for example, 2 min, 3 min, 4 min or 5 min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] Preferably, the thickness of the positive electrode layer is 30-50 μm, for example, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] Preferably, the porosity of the positive electrode layer is 30-40%, for example, it can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39% or 40%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] In the present invention, when the porosity of the positive electrode layer is controlled within the above preferred range, it is beneficial for the sulfide electrolyte dispersion to fully and evenly infiltrate the positive electrode layer, and is beneficial for forming a conductive circuit in the composite solid positive electrode.

[0026] Preferably, the sulfide electrolyte includes Li3PS4, nLi2S·(100-n)P2S5, Li 10 GeP2S 12 (LGPS) and at least one of Li6PS5X, wherein 70≤n≤80, and X includes at least one of Cl, Br and I.

[0027] The n may be, for example, 70, 75 or 80, such as 70Li2S·30P2S5, 80Li2S·20P2S5 or 75Li2S·25P2S5.

[0028] Preferably, the non-polar solvent comprises at least one of toluene, p-xylene, benzene, n-hexane, methylcyclohexane, n-octane, petroleum ether, gasoline, heptane, cyclohexane, carbon disulfide and propylene chloride.

[0029] Preferably, the sulfide electrolyte dispersion further includes a binder, and the binder is miscible with the non-polar solvent.

[0030] In the present invention, a binder is introduced into the sulfide electrolyte dispersion in order to stabilize the sulfide electrolyte and avoid sedimentation of the sulfide electrolyte.

[0031] Preferably, in the sulfide electrolyte dispersion, the binder includes at least one of SBR (styrene butadiene rubber), NBR (nitrile butadiene rubber), HNBR (hydrogenated nitrile butadiene rubber), SEBS (styrene-ethylene-butylene-styrene block copolymer) and PIB (polyisobutylene).

[0032] Preferably, in the sulfide electrolyte dispersion, the mass ratio of the binder to the sulfide electrolyte is (95-99):1, for example, it can be 95:1, 96:1, 97:1, 98:1 or 99:1, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] Preferably, the solid content of the sulfide electrolyte dispersion is 50-65%, for example, it can be 50%, 51%, 53%, 55%, 58%, 60% or 65%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In the present invention, when the solid content of the sulfide electrolyte dispersion is controlled within the above preferred range, the sulfide electrolyte dispersion is relatively stable and has an appropriate viscosity, and can fully infiltrate the positive electrode layer, so that the sulfide electrolyte is evenly distributed in the positive electrode layer.

[0035] Preferably, in step (2), the volume of the sulfide electrolyte dispersion is equal to the pore volume of the positive electrode layer.

[0036] Preferably, the drying temperature in step (2) is 60-80°C, for example, 60°C, 65°C, 70°C, 75°C or 80°C; the drying time is 3-5 min, for example, 3 min, 4 min or 5 min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0037] Preferably, in step (3), steps (1) and (2) are repeated at least once until the single-side surface loading of the positive electrode active material is ≥ 20 mg / cm 2 , for example, it can be 20 mg / cm 2, 25mg / cm 2 、30mg / cm 2 、35mg / cm 2 , 40mg / cm 2 , 45mg / cm 2 or 50mg / cm 2 The above range is not limited to the listed values, and other values ​​not listed within the above range are also applicable.

[0038] As a preferred technical solution of the present invention, the preparation method specifically comprises:

[0039] (I) A positive electrode active material, a conductive agent, a binder and a solvent are mixed and stirred to obtain a positive electrode slurry; wherein the positive electrode active material includes at least one of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium vanadate and lithium iron manganese phosphate.

[0040] (II) mixing a sulfide electrolyte, a binder and a non-polar solvent, and stirring to obtain a sulfide electrolyte dispersion having a solid content of 50-65%; wherein the sulfide electrolyte and the non-polar solvent are immiscible, and the binder is miscible with the non-polar solvent; the sulfide electrolyte comprises Li3PS4, nLi2S·(100-n)P2S5, Li 10 GeP2S 12 and at least one of Li6PS5X, wherein 70≤n≤80, X includes at least one of Cl, Br and I; the non-polar solvent includes at least one of toluene, p-xylene, benzene, n-hexane, methylcyclohexane, n-octane, petroleum ether, gasoline, heptane, cyclohexane, carbon disulfide and propylene glycol; the binder includes at least one of SBR, NBR, HNBR, SEBS and PIB; the mass ratio of the binder to the sulfide electrolyte is (95-99):1.

[0041] (III) The positive electrode slurry is coated on at least one side of the current collector, and then dried at 90-110° C. for 2-5 min to obtain a positive electrode layer with a thickness of 30-50 μm and a porous structure, wherein the porosity of the positive electrode layer is 30-40%.

[0042] (IV) coating the sulfide electrolyte dispersion onto the surface of the positive electrode layer away from the current collector, allowing the sulfide electrolyte dispersion to penetrate into the pore structure of the positive electrode layer, and then drying at 60-80° C. for 3-5 min; wherein the volume of the sulfide electrolyte dispersion is equal to the pore volume of the positive electrode layer.

[0043] (V) Repeat steps (III) and (IV) at least once until the single-side surface loading of the positive electrode active material is ≥ 20 mg / cm 2, and then dried and roll-pressed to obtain the sulfide composite solid positive electrode.

[0044] In the present invention, the positive electrode slurry and the sulfide electrolyte dispersion are prepared separately and coated separately, so that the side reaction caused by direct mixing between the two can be avoided.

[0045] In a second aspect, the present invention provides a sulfide composite solid-state positive electrode, which is prepared by the preparation method described in the first aspect.

[0046] Preferably, the porosity of the sulfide composite solid-state positive electrode is ≤5%.

[0047] In a third aspect, the present invention provides an all-solid-state battery, comprising the sulfide composite solid-state positive electrode described in the second aspect.

[0048] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] The present invention provides a method for preparing a sulfide composite solid-state positive electrode. By alternating coating, the sulfide electrolyte can be evenly distributed in the positive electrode layer, and the uniform addition of the sulfide electrolyte in the high-surface-load thick positive electrode can be achieved, which can avoid the problem that the thick base electrode is formed at one time and the electrolyte cannot be fully penetrated and impregnated; at the same time, in the sulfide electrolyte dispersion of the present invention, the sulfide electrolyte is insoluble in non-polar solvents, and the microstructure of the sulfide electrolyte has not changed. In the subsequent drying process, only a lower temperature is required to remove the non-polar solvent, which has no effect on the ionic conductivity of the sulfide electrolyte, thereby avoiding the problem of reduced ionic conductivity caused by the dissolution-precipitation of the sulfide electrolyte, and no high-temperature treatment is required to improve the ionic conductivity; in addition, the preparation method of the present invention is highly operable and can be industrially large-scale production. In summary, the preparation method of the present invention can prepare a sulfide composite solid-state positive electrode with controllable surface load and high-speed lithium ion transmission channel. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 A schematic diagram of the process of preparing a sulfide composite solid-state positive electrode provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0052] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0053] In one embodiment, the present invention provides a method for preparing a sulfide composite solid positive electrode, the process of which is as follows: Figure 1 As shown, the preparation method comprises:

[0054] (1) Prepare positive electrode slurry and sulfide electrolyte dispersion respectively:

[0055] The positive electrode active material, the conductive agent, the binder 1 and the solvent are mixed to prepare a positive electrode slurry.

[0056] A sulfide electrolyte, a binder 2 and a non-polar solvent are mixed to prepare a sulfide electrolyte dispersion, wherein the sulfide electrolyte and the non-polar solvent are immiscible, and the binder 2 and the non-polar solvent are miscible.

[0057] (2) The positive electrode slurry is coated on at least one side of the current collector, and after drying, a positive electrode layer having a porous structure is obtained.

[0058] (3) coating the sulfide electrolyte dispersion onto the surface of the positive electrode layer away from the current collector, allowing the sulfide electrolyte dispersion to penetrate into the pore structure of the positive electrode layer, and then drying to obtain a composite positive electrode 1.

[0059] (4) Repeating the steps of sequentially coating the positive electrode slurry and the sulfide electrolyte dispersion at least once, and then drying and rolling to obtain the sulfide composite solid positive electrode.

[0060] Example 1

[0061] This embodiment provides a method for preparing a sulfide composite solid-state positive electrode, the preparation method comprising:

[0062] (1) LiNi 0.8 Co 0.1 Mn 0.1 O2 ternary positive electrode material, Super P Li and PVDF were added to a stirring tank in a mass ratio of 97.5:1:1.5, NMP was added to adjust the solid content to 69%, and a stirring program was set to prepare a positive electrode slurry.

[0063] (2) Li6PS5Cl sulfide electrolyte is added to another stirring tank, and toluene, a non-polar solvent that is immiscible with sulfide, is added. In addition, a small amount of binder PIB that is soluble in the non-polar solvent is added. The mass ratio of the binder to the sulfide electrolyte is 99:1. The stirring program is set to prepare a stable sulfide electrolyte dispersion with a solid content of 60%.

[0064] (3) The positive electrode slurry was coated on one side of the spread aluminum foil current collector, the scraper height was adjusted to 90 μm, and the resulting coating was dried at 100° C. for about 5 min to form a 42 μm thick positive electrode layer with a porous structure and a porosity of 35%.

[0065] (4) coating the sulfide electrolyte dispersion onto the surface of the positive electrode layer away from the current collector, allowing the sulfide electrolyte dispersion to penetrate into the pore structure of the positive electrode layer, and then drying at 80° C. for 5 min; wherein the volume of the sulfide electrolyte dispersion is equal to the pore volume of the positive electrode layer.

[0066] (5) Repeat steps (III) and (IV) 4 times until the single-side surface loading of the positive electrode active material is 23 mg / cm 2 , and then dried at 90 °C for 1 h, and roller pressed to obtain a sulfide composite solid positive electrode with a porosity of 4%.

[0067] Example 2

[0068] This embodiment provides a method for preparing a sulfide composite solid-state positive electrode, the preparation method comprising:

[0069] (1) LiNi 0.9 Co 0.05 Mn 0.05 O2 ternary positive electrode material, CNT and PDVF were added to a stirring tank in a mass ratio of 98:1:1, NMP was added to adjust the solid content to 65%, and a stirring program was set to prepare a positive electrode slurry.

[0070] (2) Li6PS5Cl sulfide electrolyte is added to another stirring tank, and a non-polar solvent p-xylene that is immiscible with sulfide is added, and a small amount of binder NBR that is soluble in the non-polar solvent is added. The mass ratio of the binder to the sulfide electrolyte is 99:1. The stirring program is set to prepare a stable sulfide electrolyte dispersion with a solid content of 50%.

[0071] (3) The positive electrode slurry was coated on one side of the spread aluminum foil current collector, and the scraper height was adjusted to 65 μm. The resulting coating was dried at 100°C for about 5 min. It was observed that there was no obvious solvent on the surface, and a 30 μm thick positive electrode layer with a porous structure was obtained, and its porosity was 33%.

[0072] (4) coating the sulfide electrolyte dispersion onto the surface of the positive electrode layer away from the current collector, allowing the sulfide electrolyte dispersion to penetrate into the pore structure of the positive electrode layer, and then drying at 80° C. for 5 min; wherein the volume of the sulfide electrolyte dispersion is equal to the pore volume of the positive electrode layer.

[0073] (5) Repeat steps (III) and (IV) 6 times until the single-side surface loading of the positive electrode active material is 25 mg / cm 2 , and then dried at 90 °C for 1 h, and roller pressed to obtain a sulfide composite solid positive electrode with a porosity of 4.9%.

[0074] Example 3

[0075] This embodiment provides a method for preparing a sulfide composite solid-state positive electrode, the preparation method comprising:

[0076] (1) LiNi 0.8 Co 0.1 Mn 0.1 O2 ternary positive electrode material, Ketjen black and PVDF were added to a stirring tank in a mass ratio of 98:1:1, NMP was added to adjust the solid content to 66%, and a stirring program was set to prepare a positive electrode slurry.

[0077] (2) Li 10 GeP2S 12 The sulfide electrolyte is added to another stirring tank, and a non-polar solvent cyclohexane that is immiscible with the sulfide is added. In addition, a small amount of binder PIB that is soluble in the non-polar solvent is added. The mass ratio of the binder to the sulfide electrolyte is 98:1. The stirring program is set to prepare a stable sulfide electrolyte dispersion with a solid content of 55%.

[0078] (3) The positive electrode slurry was coated on one side of the spread aluminum foil current collector, and the scraper height was adjusted to 110 μm. The resulting coating was dried at 100°C for about 5 min. It was observed that there was no obvious solvent on the surface, forming a 51 μm thick positive electrode layer with a porous structure and a porosity of 32%.

[0079] (4) coating the sulfide electrolyte dispersion onto the surface of the positive electrode layer away from the current collector, allowing the sulfide electrolyte dispersion to penetrate into the pore structure of the positive electrode layer, and then drying at 80° C. for 5 min; wherein the volume of the sulfide electrolyte dispersion is equal to the pore volume of the positive electrode layer.

[0080] (5) Repeat steps (III) and (IV) 6 times until the single-side surface loading of the positive electrode active material is 38 mg / cm 2 , and then dried at 90 °C for 1 h, and roller pressed to obtain a sulfide composite solid positive electrode with a porosity of 4%.

[0081] Example 4

[0082] This embodiment provides a method for preparing a sulfide composite solid-state positive electrode, the preparation method comprising:

[0083] (1) LiFeO4 positive electrode material, Ketjen black and PVDF were added into a stirring tank in a mass ratio of 98:1:1, NMP was added to adjust the solid content to 64%, and a stirring program was set to prepare a positive electrode slurry.

[0084] (2) Li 10 GeP2S 12 The sulfide electrolyte is added to another stirring tank, and a non-polar solvent cyclohexane that is immiscible with the sulfide is added. In addition, a small amount of binder PIB that is soluble in the non-polar solvent is added. The mass ratio of the binder to the sulfide electrolyte is 98:1. The stirring program is set to prepare a stable sulfide electrolyte dispersion with a solid content of 57%.

[0085] (3) The positive electrode slurry was coated on one side of the spread aluminum foil current collector, and the scraper height was adjusted to 110 μm. The resulting coating was dried at 100°C for about 5 min. It was observed that there was no obvious solvent on the surface, forming a 51 μm thick positive electrode layer with a porous structure and a porosity of 32%.

[0086] (4) coating the sulfide electrolyte dispersion onto the surface of the positive electrode layer away from the current collector, allowing the sulfide electrolyte dispersion to penetrate into the pore structure of the positive electrode layer, and then drying at 80° C. for 5 min; wherein the volume of the sulfide electrolyte dispersion is equal to the pore volume of the positive electrode layer.

[0087] (5) Repeat steps (III) and (IV) 6 times until the single-side surface loading of the positive electrode active material is 38 mg / cm 2 , and then dried at 90 °C for 1 h, and roller pressed to obtain a sulfide composite solid positive electrode with a porosity of 4%.

[0088] Example 5

[0089] The difference between this embodiment and embodiment 1 is that the solid content of the sulfide electrolyte dispersion is adjusted to 45%.

[0090] The remaining methods and parameters are consistent with those in Example 1.

[0091] Example 6

[0092] The difference between this embodiment and embodiment 1 is that the solid content of the sulfide electrolyte dispersion is adjusted to 70%.

[0093] The remaining methods and parameters are consistent with those in Example 1.

[0094] Example 7

[0095] The difference between this embodiment and embodiment 1 is that the solid content of the positive electrode slurry is adjusted so that the porosity of the positive electrode layer after drying is adjusted to 20%.

[0096] The remaining methods and parameters are consistent with those in Example 1.

[0097] Example 8

[0098] The difference between this embodiment and embodiment 1 is that the solid content of the positive electrode slurry is adjusted so that the porosity of the positive electrode layer is adjusted to 44%.

[0099] The remaining methods and parameters are consistent with those in Example 1.

[0100] Comparative Example 1

[0101] The difference between this comparative example and Example 1 is that the entire positive electrode slurry is directly coated on the surface of the aluminum foil, dried at 110°C for 1 hour, and a positive electrode layer with a porous structure is formed in one step, and then the entire sulfide electrolyte dispersion is coated on the surface of the positive electrode layer away from the current collector, and then dried and rolled to obtain a sulfide composite solid positive electrode with a porosity of 11%.

[0102] The remaining methods and parameters are consistent with those in Example 1.

[0103] Comparative Example 2

[0104] The difference between this comparative example and Example 1 is that the non-polar solvent is replaced by ethanol.

[0105] The remaining methods and parameters are consistent with those in Example 1.

[0106] Performance Testing

[0107] (1) Positive electrode ion conductivity test:

[0108] The sulfide composite solid positive electrode provided in the above examples and comparative examples was cut into φ10 mm pole pieces, and a φ10 mm blank aluminum foil was cut and placed on top of the composite positive electrode coating as a blocking electrode. The assembly pressure was 100 MPa. The impedance spectrum test was performed using an electrochemical workstation at 25°C, with a frequency range of 10 7 -0.1Hz, amplitude 5mV, and the ionic conductivity was calculated.

[0109] (2) Positive electrode discharge specific capacity test:

[0110] The sulfide composite solid positive electrode provided in the above embodiments and comparative examples was cut into pole pieces of φ10 mm, and Li6PS5Cl powder was used as the electrolyte and Li-In alloy was used as the negative electrode to assemble the mold battery, and the assembly pressure was 400 MPa.

[0111] Under the conditions of test pressure of 50MPa and test temperature of 45℃, in the voltage range of 2.0-3.7V, the mold battery was first charged at 0.1C and then discharged at 0.33C using a blue electric tester, and the first discharge specific capacity was recorded.

[0112] The test results are shown in Table 1.

[0113] Table 1

[0114]

[0115]

[0116] analyze:

[0117] It can be seen from Examples 1-4 that the sulfide composite solid positive electrode prepared by the preparation method of the present invention has high ion conductivity and high discharge specific capacity, which is close to the discharge capacity of the positive electrode material in the liquid battery.

[0118] It can be seen from Examples 1 and 5-6 that if the solid content of the sulfide electrolyte dispersion is too low, the sulfide electrolyte dispersion will be unstable and sedimentation will occur. Therefore, the sulfide electrolyte is unevenly distributed in the obtained composite positive electrode sheet, resulting in a decrease in the positive electrode ion conductivity and capacity; if the solid content of the sulfide electrolyte dispersion is too high, the viscosity will be too high, and the sulfide electrolyte dispersion will not be able to fully infiltrate the positive electrode layer, resulting in a decrease in the positive electrode ion conductivity and capacity.

[0119] It can be seen from Example 1 and Examples 7-8 that if the porosity of the positive electrode layer is too low, the amount of sulfide solid electrolyte in the composite positive electrode is insufficient, and a conductive circuit cannot be formed, resulting in a decrease in the positive electrode ion conductivity and capacity; if the porosity of the positive electrode layer is too high, the porosity of the composite electrode sheet after rolling will be too high, and an effective conductive circuit cannot be formed, thereby resulting in a decrease in the positive electrode ion conductivity and capacity.

[0120] It can be seen from Example 1 and Comparative Example 1 that when a sulfide electrolyte dispersion is coated on a thick positive electrode layer, the dispersion is difficult to evenly penetrate into the positive electrode layer, the sulfide electrolysis distribution in the thickness direction of the electrode piece is uneven, and the electrode piece cannot form an effective ion conductive circuit, resulting in a significant decrease in the positive electrode ion conductivity and capacity.

[0121] It can be seen from Example 1 and Comparative Example 2 that when ethanol solvent is used, the sulfide electrolyte and the solvent are miscible, which will lead to a decrease in the ionic conductivity of the sulfide electrolyte after drying, resulting in a lower overall ionic conductivity and capacity of the composite positive electrode.

[0122] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a sulfide composite solid positive electrode, characterized in that: The preparation method comprises: (1) coating a positive electrode slurry onto at least one surface of a current collector, and drying the positive electrode slurry to obtain a positive electrode layer having a porous structure; (2) coating a sulfide electrolyte dispersion onto a surface of the positive electrode layer away from the current collector, allowing the sulfide electrolyte dispersion to penetrate into the pore structure of the positive electrode layer, and then drying; (3) repeating step (1) and step (2) at least once, and then drying and rolling to obtain the sulfide composite solid positive electrode; The sulfide electrolyte dispersion includes a sulfide electrolyte and a non-polar solvent, and the sulfide electrolyte and the non-polar solvent are immiscible.

2. The preparation method according to claim 1, characterized in that: The positive electrode slurry comprises a positive electrode active material, a conductive agent, a binder and a solvent; Preferably, the positive electrode active material includes at least one of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium vanadate and lithium iron manganese phosphate.

3. The preparation method according to claim 1 or 2, characterized in that: The drying temperature in step (1) is 90-110° C. and the drying time is 2-5 min; Preferably, the thickness of the positive electrode layer is 30-50 μm; Preferably, the porosity of the positive electrode layer is 30-40%.

4. The preparation method according to any one of claims 1 to 3, characterized in that The sulfide electrolyte includes Li3PS4, nLi2S·(100-n)P2S5, Li 10 GeP2S 12 and at least one of Li6PS5X, wherein 70≤n≤80, and X comprises at least one of Cl, Br and I; Preferably, the non-polar solvent comprises at least one of toluene, p-xylene, benzene, n-hexane, methylcyclohexane, n-octane, petroleum ether, gasoline, heptane, cyclohexane, carbon disulfide and propylene chloride; Preferably, the sulfide electrolyte dispersion further comprises a binder, and the binder is miscible with the non-polar solvent; Preferably, in the sulfide electrolyte dispersion, the binder includes at least one of SBR, NBR, HNBR, SEBS and PIB; Preferably, in the sulfide electrolyte dispersion, the mass ratio of the binder to the sulfide electrolyte is (95-99):1; Preferably, the solid content of the sulfide electrolyte dispersion is 50-65%.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (2), the volume of the sulfide electrolyte dispersion is equal to the pore volume of the positive electrode layer; Preferably, the drying temperature in step (2) is 60-80° C. and the drying time is 3-5 min.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (3), repeat step (1) and step (2) at least once until the single-sided surface loading of the positive electrode active material coated on one side is ≥ 20 mg / cm 2 .

7. The preparation method according to any one of claims 1 to 6, characterized in that: The preparation method specifically comprises: (I) mixing a positive electrode active material, a conductive agent, a binder and a solvent, and stirring to obtain a positive electrode slurry; Wherein, the positive electrode active material includes at least one of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium vanadate and lithium iron manganese phosphate; (II) mixing a sulfide electrolyte, a binder and a non-polar solvent, and stirring to obtain a sulfide electrolyte dispersion having a solid content of 50-65%; The sulfide electrolyte and the non-polar solvent are immiscible, and the binder and the non-polar solvent are miscible; the sulfide electrolyte includes Li3PS4, nLi2S·(100-n)P2S5, Li 10 GeP2S 12 and at least one of Li6PS5X, wherein 70≤n≤80, X comprises at least one of Cl, Br and I; the non-polar solvent comprises at least one of toluene, p-xylene, benzene, n-hexane, methylcyclohexane, n-octane, petroleum ether, gasoline, heptane, cyclohexane, carbon disulfide and propylene glycol; the binder comprises at least one of SBR, NBR, HNBR, SEBS and PIB; the mass ratio of the binder to the sulfide electrolyte is (95-99):1; (III) coating the positive electrode slurry onto at least one side of the current collector, and then drying at 90-110° C. for 2-5 min to obtain a positive electrode layer having a pore structure and a thickness of 30-50 μm, wherein the porosity of the positive electrode layer is 30-40%; (IV) coating the sulfide electrolyte dispersion onto the surface of the positive electrode layer away from the current collector, allowing the sulfide electrolyte dispersion to penetrate into the pore structure of the positive electrode layer, and then drying at 60-80° C. for 3-5 min; Wherein, the volume of the sulfide electrolyte dispersion is equal to the pore volume of the positive electrode layer; (V) Repeat steps (III) and (IV) at least once until the single-side surface loading of the positive electrode active material is ≥ 20 mg / cm 2 , and then dried and roll-pressed to obtain the sulfide composite solid positive electrode.

8. A sulfide composite solid positive electrode, characterized in that: The sulfide composite solid-state positive electrode is prepared by the preparation method according to any one of claims 1 to 7.

9. The sulfide composite solid positive electrode according to claim 8, characterized in that: The porosity of the sulfide composite solid-state positive electrode plate is ≤5%.

10. An all-solid-state battery, characterized in that: The all-solid-state battery comprises the sulfide composite solid-state positive electrode according to claim 8 or 9.

Citation Information

Patent Citations

  • All-solid-state battery electrode and preparation method and application thereof

    CN111628139A

Cited By

  • Preparation method of lithium tin phosphorus sulfur solid-state battery

    CN120341399A

  • All-solid-state battery, preparation method thereof and battery module

    CN121748291A